2019
DOI: 10.1111/jnc.14673
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to increasing numbers of mild traumatic brain injury in a rodent closed‐head injury model

Abstract: The Official Journal of the International Society for Neurochemistry JNC wileyonlinelibrary.com/journal/jnc The Official Journal of the International Society for Neurochemistry JNC Front cover:Following mild traumatic brain injury (mTBI), further mild impacts can exacerbate negative outcomes. We observed unexpected patterns of damage and deficits following increasing numbers of closed-head mTBI in adult female rats. This may reflect dynamic responses to small numbers of mTBIs or a conditioning effect such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 76 publications
(93 reference statements)
3
31
0
Order By: Relevance
“…hour through 7 days [30], and 24 hours [31], although others have also found no detriment [32]. The data shown here suggests that even though mild impacts in our model were administered below the threshold seen previously in similar studies, there was still measurable neurological disturbance manifested in behavioural testing.…”
Section: Plos Onesupporting
confidence: 55%
See 1 more Smart Citation
“…hour through 7 days [30], and 24 hours [31], although others have also found no detriment [32]. The data shown here suggests that even though mild impacts in our model were administered below the threshold seen previously in similar studies, there was still measurable neurological disturbance manifested in behavioural testing.…”
Section: Plos Onesupporting
confidence: 55%
“…Findings from the behavioural data include differences in NSS in the acute phase of recovery 24 hours after final injury, but no differences between groups in the NSS at three months. Previous studies using a similar acceleration mTBI mechanism have shown NSS detriment at 1 hour through 7 days [ 30 ], and 24 hours [ 31 ], although others have also found no detriment [ 32 ]. The data shown here suggests that even though mild impacts in our model were administered below the threshold seen previously in similar studies, there was still measurable neurological disturbance manifested in behavioural testing.…”
Section: Discussionmentioning
confidence: 99%
“…As a measure of astroglial activation in human mTBI, GFAP has been shown to be a sensitive and specific marker of injury (Papa et al, ). GFAP was commonly assessed in the animal studies of this review, and demonstrated utility in detecting injury either via mRNA expression (Yu, Wergedal, Rundle, & Mohan, ), protein levels in the brain (Fehily et al, ; Viano et al, ), or in serum (Candy et al, ). Production of inflammatory cytokines is also linked with glial cell activation following injury, and was commonly assessed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…: None 14b: Namjoshi [ 63 ] M: C57BL/6 m CH [C] 2 Int. : Anabolic steroids 15a: Semple [ 58 ] M: C57BL/6 m CI [C] 1 15b: Semple [ 58 ] M: C57BL/6 m CI [C] 2 16a: Shitaka [ 39 ] M: C57BL/6 J m CI [C] 2 17a: Fehily [ 43 ] R: PVG f WD [C] 1 17b: Fehily [ 43 ] R: PVG f WD [C] 2 17c: Fehily [ 43 ] R: PVG f WD [C] 3 18a: Maynard [ 49 ] M: C57BL/6 m WD [C] 3 19a: Brooks [ 47 ] R: Wistar m FPI [O] 4 20a: Maynard [ 50 ] M: C57BL/6 J ...…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of a microglial response occurring very shortly after injury is supported by the detection of microglial activation as early as 2 h post-final injury in groups 06a [ 40 ] and 27a [ 41 ], the former of which involved a single mTBI to mice. Other timecourses that show no microglial activation at any timepoint (groups 21a [ 35 ], 12b and 5c [ 36 ], 22a-c [ 42 ], 17a and 17c [ 43 ], 13b and 9b [ 44 ], and 01a [ 45 ]) are similarly ambiguous, as they may reflect injuries which do not induce microglial activation in the white matter, injuries with delays to microglial activation in the white matter longer than the latest sampled timepoint, or injuries where microglial activation in the white matter resolved prior to the first assessment timepoint. It is important to consider that activation timecourses for experimental groups receiving multiple injuries may be misleading to directly compare with activation reported in single mTBI studies, as it is unclear if the observed activation was initiated by the final mTBI or by any of the preceding mTBIs.…”
Section: Resultsmentioning
confidence: 99%